The Importance of Institutional Arrangement to Safeguard Maritime Security and Safety in Indonesia: The Case of Marine Security and Safety Agency - Omara, Andy (SASI, 2024)
Introduction: Multiple agencies approach has been adopted by the Indonesian government to ensure maritime security and safety. The involvement of multiple actors potentially leads to overlapping authorities and an uncoordinated operation. For stakeholders at sea, such approach is inefficient, ineffective and creates confusion. The situation needs to be addressed to make more a coordinated, efficient, and effective method. This paper tries to address such an issue through institutional law lens.Purposes of the Research:  This paper aims to answer three important questions (1) How is the enforcement of security and safety at sea so far? (2) What are the implications as the many institutions involved in the enforcement of safety and security at sea? and (3) What kind of institutional arrangements to be made in the future so that law enforcement at sea becomes effective and efficient?.Methods of the Research: This study utilizes a normative legal approach. It exercises legal doctrines, relevant laws and regulations. It is also suplemented by relevant literatures, books, journals, and media coverages.Results of the Research: This paper finds that the enforcement of security and safety at sea adopts multi agencies where many institutions involved in maintaining security and safety at sea. The fact that multiple institutions simultaniously  participate in law enforcement at sea, potentially create overlapping and lack of coordination among them. This also creates confusion and disadvantage to the stakeholders. Therefore, it is necessary to reorganize the current institutional arrangements to minimize the problems on the ground.